Somebody's fool : a novel [large type] - Russo, Richard, 1949- (Russo, Richard, 1949- North Bath trilogy, 2023)
"The Pulitzer Prize-winning author of Empire Falls returns to North Bath, in upstate New York, and to the characters that captured the hearts and imaginations of millions of readers in his beloved best sellers Nobody's Fool and Everybody's Fool. Ten years after the death of the magnetic Donald "Sully" Sullivan, the town of North Bath is going through a major transition as it is annexed by its much wealthier neighbor, Schuyler Springs. Peter, Sully's son, is still grappling with his father's tremendous legacy as well as his relationship to his own son, Thomas, wondering if he has been all that different a father than Sully was to him. Meanwhile, the towns' newly consolidated police department falls into the hands of Charice Bond, after the resignation of Doug Raymer, the former North Bath police chief and Charice's ex-lover. When a decomposing body turns up in the abandoned hotel situated between the two towns, Charice and Raymer are drawn together again and forced to address their complicated attraction to one another. Across town, Ruth, Sully's married ex-lover, and her daughter Janey struggle to understand Janey's daughter, Tina, and her growing obsession with Peter's other son, Will. Amidst the turmoil, the town's residents speculate on the identity of the unidentified body, and wonder who among their number could have disappeared unnoticed"--